Combining Analytical Hierarchy Process and Geographic Information Systems for Selection of Landfill Site Location: A Case Study of Ogan Ilir Regency, Indonesia - Dwi Vina Febrim; Idarwati; Mochammad Malik Ibrahim; Dede Nurohim (Indonesian Journal of Environmental Management and Sustainability, 2026)
Landfill site selection in Ogan Ilir Regency presents significant challenges due to escalating waste generation and the risks associated with improper landfill siting. This research identifies and maps environmentally suitable locations for landfill development in Ogan Ilir Regency, South Sumatra, Indonesia, through an integrated methodology that combines the Analytic Hierarchy Process (AHP), Geographic Information Systems (GIS), and remote sensing. Ten sub-criteria were established and categorized as physical, environmental, or socioeconomic, with each assigned a weight via pairwise comparison matrices. The resulting weighted spatial layers were analyzed using a weighted linear combination technique to produce comprehensive suitability models. The analysis classified the study area into three categories: less suitable (1.81%, 4,307.73 ha), moderately suitable (74.46%, 177,404.25 ha), and highly suitable (23.73%, 56,533.78 ha) for landfill development. The framework was validated using satellite imagery and adapted to local conditions, delivering a practical decision-support tool for regional planners and decision makers to promote effective and environmentally sustainable waste management strategies.